Ecological Risk Assessment of Phthalate Esters (DBP and DEHP) in Surface Water of China - Sun, Fuhong; Tao, Yanru; Shi, Di; Yang, Jiwei; Li, Huixian; Wei, Yuan; Su, Hailei (Frontiers in Environmental Science, 2021)
As a new type of pollutants, Phthalate esters (PAEs) are common organic compound in industrial production and daily life, which are widely detected in surface water environment. Among them, dibutyl phthalate (DBP) and bis (2-ethylhexyl) phthalate (DEHP) have attracted much attention due to their harmful effects on aquatic life such as endocrine disrupting effects. In this study, the toxicity data of DBP and DEHP were collected and screened through literature research, and their water quality criteria (WQC) for protecting aquatic life were derived by species sensitivity distribution method. In addition, the distributions of DBP and DEHP in surface water environment of China were analyzed and their ecological risk levels to aquatic life in six regions were evaluated by hazard quotients (HQ) and probabilistic approaches. Besides, the ecological risk of DBP and DEHP in sediment was evaluated. The result revealed that the WQC of DBP is 12.9 μg/L (chronic criteria) and 162.9 μg/L (acute criteria); the WQC of DEHP is 1.0 μg/L (chronic criteria) and 71.8 μg/L (acute criteria), respectively. The ecological the risk of DBP and DEHP in North China and Yangtze River is relatively higher than other regions, which may have harmful effects on the aquatic environments. Compared with water, the risk level of DBP and DEHP in sediment is generally higher. So it is necessary to strengthen the water quality management. The results could provide scientific basis for ecological risk management of DBP and DEHP.